Evaluacion ecocardiografica en judocas olimpicos - Almenares Pujadas, M. E.; Berovides Padilla, O.; Silva Fernandez, J.; Gonzalez Angulo, J.; Vargas Oduardo, E. R. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2006)
Echocardiographic characteristics were studied in the 14 Cuban Judo Selection members to Sydney Olympic Games. The variable values were: left ventricle diastolic diameter (56,6 ± 3,6 mm and 52,0 ± 6,4 mm) in male and female; aortic diameter (28,1 ± 3,4 mm and 27,1 ± 3,1 mm); and left auricle diameter (29,4 ± 4,1 mm and 31,1 ± 2,7 mm). Diastolic thickness: interventricular septum (9,9 ± 1,3 mm and 8,9 ± 0,7 mm) and left ventricle posterior wall (8,3 ± 0,8 mm and 8,6 ± 0,8 mm); stroke volume (93,6 ± 11,6 ml and 83,1 ± 22,0. ml); shortening fraction (32,4 ± 4,9% and 34,4 ± 3,0%); and ejection fraction (51,9 ± 7,1% and 63,3 ± 4,0%). Judocas shows an appropriate cardiovascular adaptation to aerobic and anaerobic work.